If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -14 + 3y = 14 Combine like terms: 4 + -14 = -10 -10 + 3y = 14 Solving -10 + 3y = 14 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3y = 14 + 10 Combine like terms: -10 + 10 = 0 0 + 3y = 14 + 10 3y = 14 + 10 Combine like terms: 14 + 10 = 24 3y = 24 Divide each side by '3'. y = 8 Simplifying y = 8
| 7(x-4)(x-4)-18=10 | | x^2+16-2x-5=x^2+1 | | 9-7(x+6)=4+8(x-2)+6x | | 4(x+5)+6=2(2x+3) | | 0.07x-0.04=0.01x-0.6 | | 3X+7=5X+-13 | | 2x+x^2=84 | | (m-n+k)(m+6n-9k)= | | 7x^2+23x+6x-17-13=0 | | 5(x-2)+7=3(x+8)-x-9 | | 12x-5=-41 | | 11x+7y=-19 | | 6(3n+5)=9(6n+2)+4 | | (w+7)(w+3)= | | 7n+6=1.1 | | 2(x-3)+5x-2=10x+3+4 | | .5x-2.8=.7 | | 7n-1.1=6 | | X-4y=31 | | 7w+1w-15=17 | | 1.3z+1.5=54 | | x^2+8=70 | | 138.24+25x=173.61 | | -5(6y-4)y=-2(y-5) | | y=2(3x-1)-13 | | 7(x-4)2-18=18 | | 12=x-33.25 | | 7m-13-9m=-10 | | F(x)=6x^4+4x^3-x^2-5x-7 | | -30y= | | 7p-9=10 | | y=2(3x-1)+7 |